Brief mindfulness-based intervention of 'STOP (Stop, Take a Breath, Observe, Proceed) touching your face': a study protocol of a randomised controlled trial. Issue 11 (24th November 2020) - Liao, Yanhui; Wang, Ling; Luo, Tao; Wu, Shiyou; Wu, Zhenzhen; Chen, Jianhua; Pan, Chen; Wang, Yunfei; Liu, Yueheng; Luo, Qinghua; Guo, Xin; Xie, Liqin; et al.
Abstract : Introduction: Face-touching behaviour often happens frequently and automatically, and poses potential risk for spreading infectious disease. Mindfulness-based interventions (MBIs) have shown its efficacy in the treatment of behaviour disorders. This study aims to evaluate an online mindfulness-based brief intervention skill named 'STOP (Stop, Take a Breath, Observe, Proceed) touching your face' in reducing face-touching behaviour. Methods and analysis: This will be an online-based, randomised, controlled, trial. We will recruit 1000 participants, and will randomise and allocate participants 1:1 to the 'STOP touching your face' (both 750-word text and 5 min audio description by online) intervention group (n=500) and the wait-list control group (n=500). All participants will be asked to monitor and record their face-touching behaviour during a 60 min period before and after the intervention. Primary outcome will be the efficacy of short-term mindfulness-based 'STOP touching your face' intervention for reducing the frequency of face-touching. The secondary outcomes will be percentage of participants touching their faces; the correlation between the psychological traits of mindfulness and face-touching behaviour; and the differences of face-touching behaviour between left-handers and right-handers. Analysis of covariance, regression analysis, χ 2 test, t-test, Pearson's correlations will be applied in data analysis. We will recruit 1000 participants from April to July 2020 or until the recruitment process is complete. The follow-up will be completed in July 2020. We expect all trial results to be available by the end of July 2020. Ethics and dissemination: The study protocol has been approved by the Ethics Committee of Sir Run Run Shaw Hospital, an affiliate of Zhejiang University, Medical College (No. 20200401-32). Study results will be disseminated via social media and peer-reviewed publications. Trial registration number: NCT04330352 .